The standards of architecture in The Holy Quran - Alsada, Maryam Hussain (Journal of Islamic Sciences, 2023)
This research is summarized in the presenting the architecture standards stated by the Quranic methodology, which should never be neglected in the construction and reconstruction process, and its employment in the required manner in a way that guarantees its survival and continuity. In this research, I relied on the descriptive methodology, as it is the most appropriate methodology for humanitarian studies, and more closely related to the subject of the research. Which may explain the results as required, and i had mentioned the noble verses that state the standards of architecture in Holy Quran, and classified according to their topics in the specialized section of the study, and deduced some benefits that revolve around the noble verses by referring to the books of interpretation of the Holy Quran, and relying in transmission on the closest to the meaning and purpose of the verse, while limiting it to the inference from the verse is often, and the link between the verses according to the methods of objective interpretation. The research also focuses on clarifying the geographical, environmental, structural, and design standards of architecture. Finally, one of the most important results of this research was: that urbanization in the Holy Qur’an is not limited to physical interest only; but it includes spiritual and emotional urbanization, which is represented by faith and good morals. Moreover, the perfection of Islamic architecture lies in its continuity in preserving the content and functional purpose of the building, and applying the contents and controls that it had previously through the extension of time until the present time.